Development and evaluation of real time RT-PCR assays for detection and typing of Bluetongue virus - Richard, Yolande; Maan, Sushila; Maan, Narender Singh; Belaganahalli, Manjunatha N.; Potgieter, Abraham C.; Kumar, Vinay; Batra, Kanisht; Wright, Isabel M.; Kirkland, Peter D.; Mertens, Peter P.C. (Public Library of Science, 2016)
Bluetongue virus is the type species of the genus Orbivirus, family Reoviridae. Bluetongue viruses (BTV) are transmitted between their vertebrate hosts primarily by biting midges (Culicoides spp.) in which they also replicate. Consequently BTV distribution is dependent on the activity, geographic distribution, and seasonal abundance of Culicoides spp. The virus can also be transmitted vertically in vertebrate hosts, and some strains/serotypes can be transmitted horizontally in the absence of insect vectors. The BTV genome is composed of ten linear segments of double-stranded (ds) RNA, numbered in order of decreasing size (Seg-1 to Seg-10). Genome segment 2 (Seg-2) encodes outer-capsid protein VP2, the most variable BTV protein and the primary target for neutralising antibodies. Consequently VP2 (and Seg-2) determine the identity of the twenty seven serotypes and two additional putative BTV serotypes that have been recognised so far. Current BTV vaccines are serotype specific and typing of outbreak strains is required in order to deploy appropriate vaccines. We report development and evaluation of multiple ‘TaqMan’ fluorescence-probe based quantitative real-time type-specific RT-PCR assays targeting Seg-2 of the 27+1 BTV types. The assays were evaluated using orbivirus isolates from the ‘Orbivirus Reference Collection’ (ORC) held at The Pirbright Institute. The assays are BTV-type specific and can be used for rapid, sensitive and reliable detection / identification (typing) of BTV RNA from samples of infected blood, tissues, homogenised Culicoides, or tissue culture supernatants. None of the assays amplified cDNAs from closely related but heterologous orbiviruses, or from uninfected host animals or cell cultures.